Deep learning for determining the difficulty of endodontic treatment: a pilot study - Hamed Karkehabadi; Elham Khoshbin; Nikoo Ghasemi; Amal Mahavi; Hossein Mohammad-Rahimi; Soroush Sadr (BMC, 2024)
Abstract Background To develop and validate a deep learning model for automated assessment of endodontic case difficulty from periapical radiographs. Methods A dataset of 1,386 periapical radiographs was compiled from two clinical sites. Two dentists and two endodontists annotated the radiographs for difficulty using the "simple assessment" criteria from the American Association of Endodontists' case difficulty assessment form in the Endocase application. A classification task labeled cases as "easy" or "hard", while regression predicted overall difficulty scores. Convolutional neural networks (i.e. VGG16, ResNet18, ResNet50, ResNext50, and Inception v2) were used, with a baseline model trained via transfer learning from ImageNet weights. Other models was pre-trained using self-supervised contrastive learning (i.e. BYOL, SimCLR, MoCo, and DINO) on 20,295 unlabeled dental radiographs to learn representation without manual labels. Both models were evaluated using 10-fold cross-validation, with performance compared to seven human examiners (three general dentists and four endodontists) on a hold-out test set. Results The baseline VGG16 model attained 87.62% accuracy in classifying difficulty. Self-supervised pretraining did not improve performance. Regression predicted scores with ± 3.21 score error. All models outperformed human raters, with poor inter-examiner reliability. Conclusion This pilot study demonstrated the feasibility of automated endodontic difficulty assessment via deep learning models.